Respon Pertumbuhan Dan Produksi Bawang Merah (Allium Cepa. L.) Akibat Pemberian Asam Humat Dan Npk 16:16:16 - Muhammad Haris Hidayat; Neng Susi; Sri Utami Lestari; Vonny Indah Sari; Prastari, Cindytia (JURAGAN - Jurnal Agroteknologi, 2023)
The shallot plant is an important vegetable commodity because it contains high nutrition, raw material for medicines, and as a complement to cooking spices, and has many vitamins and acts as an enzyme activator in the body. Shallot production, especially in Riau Province, is still not sufficient for the people's needs. The low production yield is due to low soil fertility and sub-optimal cultivation methods. For this reason, efforts are needed to increase shallot yields in Riau Province. In order for the land to be productive, it is necessary to make efforts to improve it by adding ameliorants, which are materials that can increase soil fertility by improving the physical, chemical and biological conditions of the soil. The purpose of this study was to determine the effect and obtain the best dose of Humic Acid, NPK Mutiara 16:16:16 fertilizer, and its interaction on the growth and production of shallots. This research was carried out experimentally using a factorial Completely Randomized Design (CRD), which consisted of two factors, namely H (Humic Acid) which consisted of 3 levels, and factor N (NPK fertilizer) which consisted of 3 levels, and each of them had 3 repetitions, the number of experimental units is 27 plots, each plot consists of 3 plants and 2 plants as samples, so the number of plants is 27x3 = 81 plants. The parameters observed were as follows: "Plant Height" (cm), "Number of Leaves" (strands), "Number of tubers (cm2), Diameter of tubers (cm), Number of tubers (fruits) and Weight of tubers (grams). And the interaction of humic acid and NPK fertilizer with doses of H2N2 (giving 2 g/polybag of humic acid and 20 g/polybag of NPK) gives the best results.